Red yeast rice-induced severe rhabdomyolysis complicated by acute kidney injury and respiratory failure: a case report - Pengmin Zhou; Yucai Hong; Huabo Cai; Xiaoyu Zhou; Shunpeng He; Haotian Zhou; Jie Yang; Pengpeng Chen; Boming Xia; Xiong Lei; Suibi Yang; Zhongheng Zhang (Frontiers in Medicine)
Red yeast rice (RYR), a commonly used supplement with statin-like properties, is generally considered safe but may cause severe adverse effects such as rhabdomyolysis. We report a rare case of severe RYR-induced rhabdomyolysis complicated by acute kidney injury (AKI) and respiratory failure, with diaphragmatic dysfunction as a key contributing factor. A 78-year-old woman developed progressive proximal muscle weakness, dyspnea, and tea-colored urine after taking RYR (2 g/day) for 1 month. She rapidly progressed to respiratory failure requiring intubation and mechanical ventilation. Laboratory tests showed a peak creatine kinase (CK) of 112,985 U/L, serum myoglobin (>3,000 μg/L), and AKI. Bedside ultrasound demonstrated diaphragmatic dysfunction, while electromyography (EMG) revealed preserved nerve conduction. Myositis-specific and paraneoplastic antibody panels were negative. She received continuous renal replacement therapy (CRRT), plasma exchange (PE), hemoperfusion (HP), and supportive care. During hospitalization, she developed deep vein thrombosis (DVT), pneumonia, and ileus, all of which resolved with treatment. At discharge, she had been weaned from mechanical ventilation and had partially recovered renal and muscle function. At follow-up, she was stable, ambulating, and performing daily functions without symptom recurrence. Although her initial presentation mimicked immune-mediated necrotizing myopathy (IMNM), the absence of myositis-specific antibodies and clinical improvement without immunosuppressive therapy supported a diagnosis of toxic rhabdomyolysis. This case highlights the importance of recognizing supplement-related toxicity and initiating timely organ-targeted supportive care. This appears to be the first reported case of RYR-induced rhabdomyolysis complicated by both AKI and respiratory failure from diaphragmatic dysfunction.